I have this equation:

\(\displaystyle y'+ytanx=sinx\)

The integrating factor give me \(\displaystyle f=e^xcosx\)

Factor replacement and give me:

\(\displaystyle e^xcosxdy+e^xcosx(ytanx-senx)dx=0\) but the partial derivates give me:

\(\displaystyle Q_x=cosxe^x-senxe^x\) and \(\displaystyle Q_y=e^xsenx\)

Thanks

\(\displaystyle y'+ytanx=sinx\)

The integrating factor give me \(\displaystyle f=e^xcosx\)

Factor replacement and give me:

\(\displaystyle e^xcosxdy+e^xcosx(ytanx-senx)dx=0\) but the partial derivates give me:

\(\displaystyle Q_x=cosxe^x-senxe^x\) and \(\displaystyle Q_y=e^xsenx\)

Thanks

Last edited: